Pengaruh Penggunaan Video Pembelajaran Terhadap Motivasi dan Hasil Belajar Siswa Kelas VII Mata Pelajaran Sejarah Kebudayaan Islam di MTsN 3 Kota Padang - Shahfitri, Rahma Diyanti; Eldarni, Eldarni; Hendri, Nofri; Pratiwi, Rahmi (Indo-MathEdu Intellectuals Journal, 2025)
The learning of Islamic Cultural History (SKI) at MTsN 3 Kota Padang still faces obstacles, particularly regarding limited learning resources, the complexity of the material, as well as low student motivation and learning outcomes. This study aims to determine the effect of using learning videos on the motivation and learning outcomes of Grade VII students. The study uses a quantitative approach with a Quasi Experimental Nonequivalent Control Group Design. The research subjects were 61 students, consisting of 30 students in the experimental class using learning videos and 31 students in the control class using PowerPoint media. Data were collected through learning motivation questionnaires and learning outcome tests, then analyzed using Independent Sample t-test, Welch’s t-test, and MANOVA. The analysis results showed a significance value of 0.000 < 0.05, which means that the use of learning videos has a significant effect on students' motivation and learning outcomes.